2017
DOI: 10.1080/09540121.2017.1290211
|View full text |Cite
|
Sign up to set email alerts
|

Caring for youth living with HIV across the continuum: turning gaps into opportunities

Abstract: With the increasing proportion of youth living with human immunodeficiency virus (YLHIV) and the aging of the perinatally infected population, there is a need for clinical services that are "youth friendly" to address the multiple challenges YLHIV face in terms of engagement in care and maintenance of combination antiretroviral therapy (cART). Little is known about how and where YLHIV receive their care. Further, the impact of the care structure on engagement and retention outcomes for YLHIV is ill defined. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 36 publications
(35 reference statements)
1
17
0
Order By: Relevance
“…Additional help can be provided by the clinic to female patients through support services such as medical case management and counseling [35]. In general, the younger patient population (<30 years old) has been a challenging group to retain in HIV care as noted by Griffith et al [36]. This gap in retention is due to many barriers such as unemployment, unstable housing, mental health issues, and substance use.…”
Section: Discussionmentioning
confidence: 99%
“…Additional help can be provided by the clinic to female patients through support services such as medical case management and counseling [35]. In general, the younger patient population (<30 years old) has been a challenging group to retain in HIV care as noted by Griffith et al [36]. This gap in retention is due to many barriers such as unemployment, unstable housing, mental health issues, and substance use.…”
Section: Discussionmentioning
confidence: 99%
“…7 YHIV including those who struggle with sustaining adherence to oral ARVs may be an ideal target population for such an intervention within the setting of a youth-friendly program. 8 Critically absent from existing data is the youth perspective on LAARV technologies. There is a knowledge gap on the readiness of YHIV to adopt and adhere to LAARV.…”
Section: Introductionmentioning
confidence: 99%
“…Prior review of routine care at GHESKIO found 68% of adolescents were retained in care at 12 months, less than the 93% follow-up achieved in our study (Reif et al, 2016). Loss and inconsistent HIV caredisengaging and re-engaging from regular follow-upis common among adolescents (Griffith & Agwu, 2017;Mark et al, 2017;Murray et al, 2017). Completing VL testing over multiple visits risks patient loss before poor outcomes can be identified and addressed.…”
Section: Viral Load Outcomesmentioning
confidence: 53%